Investigating the relationship between health-promoting lifestyle behaviors and hopelessness among medical and non-medical students - Özgür Polat, Pelin; Çelik, Mustafa (Journal of Surgery and Medicine, 2021)
Background/Aim: Investigating the correlates of healthy lifestyle habits is essential to promote healthy behaviors in university students to be able to prevent developing non-communicable diseases in the long-term. The primary aim of this research was to investigate whether hopelessness is associated with health-promoting lifestyle behaviors among university students. Also, healthy lifestyle habits of medical students were compared with those of students from different fields of study. Methods: Four hundred and thirty-five undergraduate students from the Faculties of Medicine and Science and Literature participated in a paper-based cross-sectional study. The data were collected with the demographic information sheet, Health-Promoting Lifestyle Profile II (HPLP II), and Beck Hopelessness Scale (BHS), and analyzed using SPSS 22 statistics software. Results: There were significant negative correlations between BHS scores and HPLP II total (r=-0.39) and all subscale scores, including health responsibility (r=-0.22), physical activity (r=-0.18), nutrition (r=-0.17), spiritual growth (r=-0.53), interpersonal relations (r=-0.30), and stress management (r=-0.25; P<0.001 for all). In addition, medical students had higher physical activity (95% CI [0.64, 2.50], t(406.03)=3.33, P<0.001) and lower interpersonal relations (95% CI [-1.73, -0.10], t(429.74)=-2.22, P=0.027) scores than their non-medical counterparts. Conclusion: This study investigating the relationship between hopelessness and health-promoting lifestyle behaviors among medical and non-medical students revealed that negative expectations about the possible consequences of potential behaviors are associated with retention of activities that can improve health in the long-term. Considering their reported weakness in interpersonal relationships, medical education should provide support to the students in improving their social support network to enhance their health and well-being.